2009
DOI: 10.1016/j.polymer.2009.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured polystyrene-block-poly(4-vinyl pyridine)(pentadecylphenol) thin films as templates for polypyrrole synthesis

Abstract: Polypyrrole has been chemically synthesized on thin film nanostructures obtained from comb-shaped supramolecules of polystyrene-block-poly(4-vinyl pyridine) (PS-b-P4VP) hydrogen bonded with pentadecylphenol (PDP). PDP was washed from thin films of cylindrical and lamellar self-assembled combcopolymer systems, which resulted in removal of the upper layers of microdomains, leaving single cylindrical and lamellar layers covering a substrate, with P4VP segregated at the bottom as well as at the free air interface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The ability of block copolymers to spontaneously form microphase-separated structures with length scales of 10–100 nm indeed makes them extensive applications in nanoscience, such as pore materials [1], drug delivery [2], and templates [3, 4]. Recently, researchers are devoted to design block copolymers with different architectures to engineer functional materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of block copolymers to spontaneously form microphase-separated structures with length scales of 10–100 nm indeed makes them extensive applications in nanoscience, such as pore materials [1], drug delivery [2], and templates [3, 4]. Recently, researchers are devoted to design block copolymers with different architectures to engineer functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Coil-comb copolymers, which self-assemble at a length scale of a few nanometers, can be constructed by attaching oligomers or small molecules to polymers via covalent bond and noncovalent-bonding interactions, for example, hydrogen bonding, electrostatic interactions, or metal coordination [1, 3, 4, 1027]. They have potential applications such as in electrical, biological, and other functional materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly reported small molecules for such supramolecular complexes are 2-(4′-hydroxybenzeneazo)benzoic acid (HABA) and 3-pentadecylphenol (PDP). Tung et al [21,31] and ten Brinke et al [32,33] have investigated the structure-within-structure morphologies in thin films involving the interaction of PDP with P4VP. Tung et al have demonstrated the correlation between the morphology orientation in thin films and the volume fraction of P4VP/PDP block [21].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, an advantage of the chemical method is that it can be used to polymerize pyrrole monomers onto a polymeric template, for example to obtain material with better mechanical properties or to obtain nanostructured polypyrrole [16,17]. Especially poly(4-vinylpyridine) (P4VP) has been used in this respect, due to the ability of P4VP to form complexes with various oxidants, while these retain their ability to oxidize pyrrole [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%